Research progress of paclitaxel nanodrug delivery system in the treatment of triple-negative breast cancer - Jia-xin Qiao; Dong-yan Guo; Huan Tian; Zhan-peng Wang; Qiang-qiang Fan; Yuan Tian; Jing Sun; Xiao-fei Zhang; Jun-bo Zou; Jiang-xue Cheng; Fei Luan; Bing-tao Zhai (Materials Today Bio)
Triple-negative breast cancer (TNBC) is the most aggressive subtype of breast cancer, characterized by the loss or low expression of estrogen receptor (ER), human epidermal growth factor receptor 2 (HER2) and progesterone receptor (PR). Due to the lack of clear therapeutic targets, paclitaxel (PTX) is often used as a first-line standard chemotherapy drug for the treatment of high-risk and locally advanced TNBC. PTX is a diterpenoid alkaloid extracted and purified from Taxus plants, functioning as an anticancer agent by inducing and promoting tubulin polymerization, inhibiting spindle formation in cancer cells, and preventing mitosis. However, its clinical application is limited by low solubility and high toxicity. Nanodrug delivery system (NDDS) is one of the feasible methods to improve the water solubility of PTX and reduce side effects. In this review, we summarize the latest advancements in PTX-targeted NDDS, as well as its combination with other codelivery therapies for TNBC treatment. NDDS includes passive targeting, active targeting, stimuli-responsive, codelivery, and multimode strategies. These systems have good prospects in improving the bioavailability of PTX, enhancing tumor targeting, reducing toxicity, controlling drug release, and reverse tumor multidrug resistance (MDR). This review provides valuable insights into the clinical development and application of PTX-targeted NDDS in the treatment of TNBC.